Encyclopedia of rainforests - Jukofsky, Diane; Rainforest Alliance (Westport, Conn. ; London : Oryx Press, 2002)
"Explore the magic and mystery of the world's tropical rainforests in this fascinating volume that brings to life the plants, animals, and people that inhabit this fragile ecosystem. Focusing on the rainforests situated in the land area between the Tropic of Cancer and the Tropic of Capricorn, the encyclopedia provides a rich and thorough presentation of the scientific, political, and economic significance of the region. Entries cover 100 forest-dwelling, indigenous groups and numerous naturalists, scientists, explorers, and activists from around the world. The principal causes of deforestation and efforts to save the tropical forests are discussed in detail. The encyclopedia also offers extensive lists of rainforest resources including print and video materials, websites, government agencies, conservation groups and international organizations, and associations and government agencies in the United States and Canada."--BOOK JACKET.
An introduction to tropical forests : understanding a mysterious place on the planet -- Tropical forest distribution maps -- The world's tropical forests : where they are, how much is left, how fast they are vanishing -- pt. 1. Tropical forest wildlife -- pt. 2. Tropical forest plants -- pt. 3. People and tropical forests -- pt. 4. Saving tropical forests -- pt. 5. Rainforest resources.
Includes bibliographical references (p. 243-255) and index.
Keywords: Rain forests -- Encyclopedias